Adaptive sequential experimentation technique for 3³ factorial designs based on revised simplex search. (1st September 2010) - Siddiqui, Mubashir; Yang, Kai
This paper is an extension to the work carried out in the field of sequential experimentation strategy by Siddiqui and Yang (2009). The methodology presented in this paper deals with expensive industrial experiments under the constraint of limited testing budget. This research focuses on involving three factors, each being at three levels. Another constraint appropriately assumed for these experiments is that of inadequate prior knowledge of the system, i.e., the behaviour of the system is not very well known to the experimenter. The aim of this research is to explore high quality parameter space in a minimum number of experimental runs in such situations. The explained experimentation strategy uses adaptive one factor at a time method, simplex downhill method, and response surface method.